Flexible and porous 2D layered structures based on mixed-linker metal–organic frameworks for gas sorption studies. Issue 25 (2nd June 2021) - Dissem, Nour; Essalhi, Mohamed; Ferhi, Najmeddine; Abidi, Adela; Maris, Thierry; Duong, Adam
Abstract : New mixed-linkers and porous materials with the features of HOFs/MOFs were synthesized and used to study gas sorption properties. Abstract : Layered structures of flexible mixed-linker metal–organic frameworks termed IRHs-(4 and 5 ) (IRH = Institut de Recherche sur l'Hydrogène) were synthesized by mixing cyclam, tetrakis(4-carboxyphenyl)benzene (TCPB), and copper and zinc metal salts respectively. The new materials characterized by single-crystal X-ray diffraction exhibited the features of HOFs and MOFs. Their structures are formed by coordination and hydrogen bonds that link metallocyclam (with Cu or Zn) and TCPB to a 2D sheet which is further packed to form a 3D structure with 1D microchannels. Remarkably, the as-synthesized IRHs-(4 and 5 ) contain DMF in the channels that can be exchanged with DCM and afterward removed from the framework by heating without losing their single-crystallinity. This enabled an easy elucidation of the structural transformations by single-crystal and powder X-ray diffraction analyses. Experimental studies of single-component adsorption isotherms of pure CO2, CH4, and N2 gases have been carried out for all activated IRHs. Based on the obtained adsorption isotherms, theoretical calculations using Ideal Adsorbed Solution Theory (IAST) have been performed to predict the selectivity of equimolar CO2 /CH4 and CO2 /N2 (1 : 1) binary mixtures. The simulations predicted outstanding selectivity for CO2 /N2 than for CO2 /CH4 at low pressures, reaching 185 for IRH-4 and 130 for IRH-5 at 1 bar.